2003
DOI: 10.1191/1352458503ms949oa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visual information on step-tracking movements in patients with intention tremor due to multiple sclerosis

Abstract: The effect of visual information on step-tracking movements was studied in 18 patients with intention tremor due to multiple sclerosis (MS) and 15 healthy controls. Parricipants performed a slow wrist step-tracking task with stationary targets under five visual feedback conditions. The display of the target and movement cues was selectively withdrawn to examine the effects of visual information on intention tremor and movement accuracy. Results showed that intention tremor was most pronounced when visual displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
9
34
0
Order By: Relevance
“…This observation may be related to the nature of the circular drawing task, which is a visually guided movement requiring continuous error correction. Our previous studies (Liu et al, 1997;Feys et al, 2003Feys et al, , 2006 showed that MS tremor is clearly enhanced when visual information of both target and hand position is available, most likely because the induction of voluntary error correction movements leads to an increase of overall involuntary intention tremor amplitude. During circular spiral drawing, it is thought that MS patients visually detected spatial errors easier in the radial direction, perpendicular to the circle template, rather than in its tangential direction.…”
Section: The Influence Of Drawing Patternsmentioning
confidence: 98%
“…This observation may be related to the nature of the circular drawing task, which is a visually guided movement requiring continuous error correction. Our previous studies (Liu et al, 1997;Feys et al, 2003Feys et al, , 2006 showed that MS tremor is clearly enhanced when visual information of both target and hand position is available, most likely because the induction of voluntary error correction movements leads to an increase of overall involuntary intention tremor amplitude. During circular spiral drawing, it is thought that MS patients visually detected spatial errors easier in the radial direction, perpendicular to the circle template, rather than in its tangential direction.…”
Section: The Influence Of Drawing Patternsmentioning
confidence: 98%
“…The cooling interventions applied in our present study are thought to lead to substantial functional improvements, because the tremor measures of the step tracking task have been shown to be closely related to clinical ratings of intention tremor during the finger to nose test or pouring water. 15 However, it must be noted that the reported cooling interventions may be less effective in patients with MS who have considerable proximal tremor during the performance of functional activities requiring movements in the proximal joints. It is also unclear whether patients with MS who have very severe tremor would experience the same benefits of the moderate cooling intervention as was reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Step tracking task The wrist step tracking task and data analysis were identical to those in previous studies, 15 and are summarised here. Participants were seated in front of a computer screen with their forearm and hand placed in a wrist orthosis, which was fixed to the arm of the chair.…”
Section: Cooling Intervention and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations